2023
DOI: 10.1021/jacs.3c10784
|View full text |Cite
|
Sign up to set email alerts
|

One-step Formation of Urea from Carbon Dioxide and Nitrogen Using Water Microdroplets

Xiaowei Song,
Chanbasha Basheer,
Yu Xia
et al.

Abstract: Water (H 2 O) microdroplets are sprayed onto a graphite mesh covered with a CuBi 2 O 4 coating using a 1:1 mixture of N 2 and CO 2 as the nebulizing gas. The resulting microdroplets contain urea [CO(NH 2 ) 2 ] as detected by both mass spectrometry and 13 C nuclear magnetic resonance. This gas−liquid−solid heterogeneous catalytic system synthesizes urea in one step on the 0.1 ms time scale. The conversion rate reaches 2.7 mmol g −1 h −1 at 25 °C and 12.3 mmol g −1 h −1 at 65 °C, with no external voltage applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The Zare group recently showed a related reaction that is the formation of urea from droplets in the presence of N 2 and CO 2 . 154…”
Section: Consequences Of Water Electrificationmentioning
confidence: 99%
“…The Zare group recently showed a related reaction that is the formation of urea from droplets in the presence of N 2 and CO 2 . 154…”
Section: Consequences Of Water Electrificationmentioning
confidence: 99%
“…119,120 Moreover, the electric field at contact interfaces can drive the transport and diffusion of charged species, such as electrons. 121,122 Recent studies have suggested that the high-intensity electric field on the surface of water microdroplets is the driving force for electron transfer and subsequent formation of H 2 O 2 in sprayed water. 43,123,124 This electric field also exists at water–oil contact interfaces, and the derived electron transfer can catalyze the generation of reactive oxygen species (ROS) for degrading hexadecane.…”
Section: Fundamentals Of Contact-electro-catalysismentioning
confidence: 99%
“…The resultant seawater microdroplets are often referred to as sea spray aerosols with a diameter less than 10 μm, and larger diameter microdroplets that have very short atmospheric lifetimes are also produced . Sprayed water microdroplet interfaces possess a remarkable ability to greatly enhance chemical reactions compared with bulk-phase water, or to drive spontaneous reactions that are impossible to occur in bulk-phase water. In particular, the aromatic transformation can be significantly accelerated on water microdroplets. , Therefore, the oceanic wave energy has the potential to transform the dispersed matter in seawater mediated by the interfaces of seawater microdroplets in breaking waves. However, PyC transformation at the interfaces of seawater microdroplets has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%